Occupational health complaints and demographic features of farmers exposed to agrochemicals during agricultural activity - Dhananjayan Venugopal; Ravichandran Beerappa; Deepika Chauhan; Panjakumar Karunamoorthy; Mala Ambikapathy; Thamaraikannan Mohankumar; Avinash Gaikwad; Shridhar Kondhalkar (BMC Public Health)
Abstract Background This cross-sectional study evaluates occupational health hazards among farmers’ exposure to pesticides in Chikkaballapura, Karnataka, India, focusing on health complaints, demographic factors, occupational history and pesticide-handling practices. Methods A total of 226 participants were recruited, comprising 109 exposed farmers and 117 unexposed controls matched by age and gender. Structured questionnaires addressing demographics,and lifestyle characteristics, pesticide application practices, management procedures, and health complaints were used to gather data. Results Significant demographic disparities emerged, with a higher prevalence of younger individuals (≤ 30 years) in the exposed group (32%) than in the unexposed (18%, p = 0.002). Education levels also differed: 12% of exposed farmers had postgraduate education compared to 3% of the unexposed group (p = 0.009). Dietary practices and lifestyle characteristics like chewing tobacco, drinking alcohol, and smoking did not significantly differ between groups. Occupational practices revealed critical safety gaps. The use of personal protective equipment (PPE) was limited, with only 27% of exposed farmers reporting the use of masks, 20% wearing goggles, and 15% using gloves. Many exposed farmers engaged in high-risk tasks, including pesticide mixing (62%) and weekly pesticide applications (52%), often without the use of PPE. Health complaints were significantly more common in the exposed group: 35% reported fatigue (compared to 20% in controls, χ² = 5.51, p = < 0.05). In contrast, respiratory problems were absent in the control group and evident in 9% of the exposed group. Musculoskeletal issues, including backache (32%), and neck pain (36%), were notably higher among exposed farmers. Dermatological symptoms like burns (21%, χ² = 12.9, p = < 0.05), blisters (15%, χ² = 4.85, p < 0.05), and eye issues, including irritation (11%, χ² = 5.60, p < 0.05) and blurred vision (8%, χ² = 4.55, p < 0.05), were also significantly elevated among exposed farmers. These findings underscore the urgent need for comprehensive interventions, including regulatory policies to improve access to PPE, safety training, and targeted educational programs for younger and less-educated farmers. Conclusion This study contributes essential data for developing targeted, context-specific preventive strategies to safeguard health in rural farming communities. In order to evaluate the long-term health effects of pesticide exposures, future research should look into pesticide residue monioring in enviornmental and biological samples, demographic, socioeconomic, and occupational factors that shape exposure risk, thereby informing policies to protect agricultural workers.